2019
DOI: 10.1029/2018gc008102
|View full text |Cite
|
Sign up to set email alerts
|

Badly Behaved Detrital (U‐Th)/He Ages: Problems With He Diffusion Models or Geological Models?

Abstract: Dispersion in apatite (U‐Th)/He ages makes extracting thermochronological information challenging. This is particularly problematic for constraining the thermal history of sedimentary basins, as the total amount of heating during burial can be small and at the limits of the sensitivity of the apatite (U‐Th)/He system in apatite, but undetectable with other thermochronometric systems. Here we explore the importance of the differences in predepositional thermal histories for individual crystals and the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Thermal history information should only be derived from bedrock samples that exhibit date-eU and/or date-grain size patterns, including uniform dates regardless of eU or grain size values (Flowers & Kelley, 2011). Samples yielding overdispersed (U-Th)/He dates uncorrelated with eU or grain size should either not be modeled or more information is required to understand the date scatter (Flowers & Kelley, 2011;Fox et al, 2019).…”
Section: /2018tc005312mentioning
confidence: 99%
“…Thermal history information should only be derived from bedrock samples that exhibit date-eU and/or date-grain size patterns, including uniform dates regardless of eU or grain size values (Flowers & Kelley, 2011). Samples yielding overdispersed (U-Th)/He dates uncorrelated with eU or grain size should either not be modeled or more information is required to understand the date scatter (Flowers & Kelley, 2011;Fox et al, 2019).…”
Section: /2018tc005312mentioning
confidence: 99%
“…Hence, it should be considered whether partial/total ZHe resetting of radiation damaged zircons might have occurred, below nominal closure temperatures, in slowly coooled bedrock samples prior to tectonic unroofing or after depositional burial in the basin (Fosdick et al, ; Reiners, ). Radiation damaged zircons in the source region are susceptible to resetting at lower temperatures and may have been delivered to the basin before exhumation of the nominal fossil partial retention zone (PRZ) (Fox, Dai, & Carter, ; Guenthner et al, ). Post depositional resetting is unlikely, expect in heavily radiation damaged zircons, as estimates of basin fill thickness of <3.5 km and apatite fission‐track thermal modeling results from the Ager Basin suggest maximum burial temperatures of <140°C (Fillon et al, ; Gómez‐Gras et al, ).…”
Section: Potential Detrital Zircon Sourcesmentioning
confidence: 99%
“…6). The U, Th, and Sm concentrations, often combined into a single term, "effective uranium" (eU), have been used a proxy for radiation damage within a crystal, and age versus eU correlations are commonly used for interpretation of age scatter and thermal history inverse modeling (e.g., Guenthner et al, 2013;Fox et al, 2019). Therefore, accurate knowledge of volume has cascading effects from mass to eU concentration and age interpretation (Fig.…”
Section: Mass and Eumentioning
confidence: 99%
“…It has been shown that due to uncertainties in grain geometry, stopping distances, and parent nuclide zonation and variability, this correction can contribute > 50 % of the total analytical uncertainty (Farley and Stockli, 2002). Similarly, low error, highly dispersed apatite (U-Th) / He ages are problematic for robust interpretation and time-temperature modeling (e.g., Fox et al, 2019). The observation that the scatter of measured ages in even well-understood samples exceeds expectation based on analytical errors, combined with the knowledge that the above simplifications will not always hold, has led to the practice of Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation